1997
DOI: 10.1074/jbc.272.28.17744
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Targeting of the Agonist-stimulated m2 Muscarinic Acetylcholine Receptor to Caveolae in Cardiac Myocytes

Abstract: In cardiac myocytes, as well as specialized conduction and pacemaker cells, agonist binding to muscarinic acetylcholine receptors (mAchRs) results in the activation of several signal transduction cascades including the endothelial isoform of nitric-oxide synthase (eNOS) expressed in these cells. Recent evidence indicates that, as in endothelial cells, eNOS in cardiac myocytes is localized to plasmalemma caveolae, specialized lipid microdomains that contain caveolin-3, a musclespecific isoform of the scaffoldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
168
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(181 citation statements)
references
References 38 publications
12
168
1
Order By: Relevance
“…This finding is consistent with previously described agonist-induced caveolar targeting of m2 muscarinic and kinin B1 receptors (34,35) but differs from prior descriptions of cardiomyocyte ␤2AR as being located entirely in the caveolar-rich fractions of cultured neonatal rat cardiomyocytes (29,31). Although the h-␤2AR transgenic model may, like any overexpression or transfection system, generate nonphysiological results, other possible explanations for these differences include species differences between rodent and human ␤2AR, developmental differences between neonatal and adult cardiomyocytes (25), the total absence of intrinsic catecholamine stimulation and contractile activity in quiescent tissue culture, and altered ␤2AR localization after enzymatic cardiomyocyte isolation (25).…”
Section: Discussionsupporting
confidence: 81%
“…This finding is consistent with previously described agonist-induced caveolar targeting of m2 muscarinic and kinin B1 receptors (34,35) but differs from prior descriptions of cardiomyocyte ␤2AR as being located entirely in the caveolar-rich fractions of cultured neonatal rat cardiomyocytes (29,31). Although the h-␤2AR transgenic model may, like any overexpression or transfection system, generate nonphysiological results, other possible explanations for these differences include species differences between rodent and human ␤2AR, developmental differences between neonatal and adult cardiomyocytes (25), the total absence of intrinsic catecholamine stimulation and contractile activity in quiescent tissue culture, and altered ␤2AR localization after enzymatic cardiomyocyte isolation (25).…”
Section: Discussionsupporting
confidence: 81%
“…activation of a number of cell-surface receptors including members of the GPCR superfamily such as the muscarinic acetylcholine receptor and B2 bradykinin receptor (11,13). In contrast to this dynamic behavior, we find that, independent of ligand activation, the mammalian GnRHR is constitutively localized to non-caveolar lipid rafts in the gonadotrope-derived ␣T3-1 cell line.…”
Section: Figmentioning
confidence: 39%
“…Herein, we find that unlike other GPCRs, such as the muscarinic acetylcholine receptor and B2 bradykinin receptor that are uniformly distributed throughout the plasma membrane and localize to caveolae only in the presence of ligand (11,13), the GnRHR constitutively resides in a low density membrane microdomain in both the gonadotrope-derived ␣T3-1 cell line that expresses the endogenous GnRHR gene (32) and Chinese hamster ovary (CHO) cells. We also find that c-raf kinase, a target of GnRHR signaling, is constitutively, but not exclusively, localized to low density membrane fractions.…”
mentioning
confidence: 99%
“…de Weerd and Leeb-Lundberg (29) have shown that activation of bradykinin B 2 receptors that couple to G q/11 and G i in DDT 1 MF-2 smooth muscle cells increased G␣ q and G␣ i binding to caveolin with a time course similar to that elicited by ACh in intestinal smooth muscle cells. Some receptors, for example, m2 receptors in cardiac myocytes (31) and CCK-A receptors in pancreatic acinar cells (52) also bind to caveolin upon activation. In the present study, m2 but not m3 receptors bound to caveolin-3 upon activation with ACh, implying that translocation of receptors to caveolae was not a prerequisite for desensitization of response, which was observed upon selective activation of either m2 or m3 receptors.…”
Section: Discussionmentioning
confidence: 99%